A Lightweight Mobile Service for Context Representation through an IoT-oriented Ontology - Veiga, Ernesto Fonseca; Ferreira, Lucas Balbino de Melo; Arruda, Mayke Ferreira; Macedo, Alessandra Alaniz; Bulcão-Neto, Renato de Freitas (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
ABSTRACT.